Analisis Perencanaan Strategis, Penjaminan Mutu Pendidikan, dan Kinerja Lembaga - Pryditzia Presdiranti; Samsul Susilawati (Al-Kindi, 2026)
This study aims to analyze the relationship between strategic planning, education quality assurance, and institutional performance. This study uses a qualitative research method with a descriptive approach through a literature study. Data was obtained from scientific journals, books, and relevant literature that discuss the concept of strategic planning, quality assurance systems, and performance management of educational institutions. The results of the study show that strategic planning plays an important role in determining the direction, goals, and priorities of quality programs that are the basis for the implementation of quality education. Meanwhile, quality assurance functions as an evaluative mechanism that ensures that the institution's strategy is implemented consistently through the PPEPP (Determination, Implementation, Evaluation, Control, and Improvement) cycle. The integration between the two has been proven to be able to improve management effectiveness, learning quality, and institutional accountability. Therefore, the integration of strategic planning and quality assurance is a key factor in creating superior, sustainable, and adaptive institutional performance to change.